Respuesta :
Answer: Choice D)
S(x) = 6x^2 - 20x
-----------------------------------------------
-----------------------------------------------
Explanation:
x = side length of base
x*x = x^2 = area of base
The top also has an area of x^2 since the base and top are both congruent squares. The total base area is x^2+x^2 = 2x^2
The height h is 5 inches shorter than the base, so
h = (base length) - 5
h = x-5
Each lateral side is of area h*x = (x-5)*x = x^2-5x
There are 4 lateral sides
Total lateral area = 4*(area of one lateral side)
Total lateral area = 4*(x^2-5x)
Total lateral area = 4*x^2-4*5x
Total lateral area = 4*x^2-20x
Add the total lateral area (4x^2-20x) to the total base area (2x^2)
Doing so gets us
S(x) = Total Surface Area
S(x) = (Area of bases) + (area of lateral sides)
S(x) = (2x^2) + (4x^2-20x)
S(x) = (2x^2+4x^2) - 20x
S(x) = 6x^2 - 20x
which is why the answer is choice D
S(x) = 6x^2 - 20x
-----------------------------------------------
-----------------------------------------------
Explanation:
x = side length of base
x*x = x^2 = area of base
The top also has an area of x^2 since the base and top are both congruent squares. The total base area is x^2+x^2 = 2x^2
The height h is 5 inches shorter than the base, so
h = (base length) - 5
h = x-5
Each lateral side is of area h*x = (x-5)*x = x^2-5x
There are 4 lateral sides
Total lateral area = 4*(area of one lateral side)
Total lateral area = 4*(x^2-5x)
Total lateral area = 4*x^2-4*5x
Total lateral area = 4*x^2-20x
Add the total lateral area (4x^2-20x) to the total base area (2x^2)
Doing so gets us
S(x) = Total Surface Area
S(x) = (Area of bases) + (area of lateral sides)
S(x) = (2x^2) + (4x^2-20x)
S(x) = (2x^2+4x^2) - 20x
S(x) = 6x^2 - 20x
which is why the answer is choice D